Structural, Optical and Photoconductivity Studies on Benzoyl Glycine NLO Single Crystals - Suresh, S.; Raman, A.; Vasanthakumari, R. (Asian Journal of Chemistry, 2010)
Single crystals of benzoyl glycine (BG) with high degree of transparency were grown by slow evaporation technique. Powder crystal X-ray diffraction analysis reveals that the crystal belongs to orthorhombic system with the space group P212121. The physical parameters have been determined for the grown crystal. The optical absorption study reveals the transparency of the crystal in the entire visible region and the cut off wavelength was found to be 240 nm. The optical band gap was found to be 3.75 eV. The dependence of extinction coefficient (k) and refractive index (n) on the wavelength have also been reported. The dielectric constant was also studied as a function of frequency at room temperature. The photo conductivity study proves that benzoyl glycine crystal exhibits negative photoconductivity.